Application of Herbal Traditional Chinese Medicine in the Treatment of Acute Kidney Injury - Li, Hai-Di; Meng, Xiao-Ming; Huang, Cheng; Zhang, Lei; Lv, Xiong-Wen; Li, Jun (Frontiers in Pharmacology, 2019)
Acute kidney injury (AKI) is clinical syndrome characterized by a rapid loss of renal function, and it may further develop into the chronic kidney damage (CKD) or even end-stage renal disease (ESRD). AKI becomes a global health problem associated with high morbidity and great cost of treatment, and there is no specific and effective strategy to treat AKI. In recent years, Traditional Chinese Medicine (TCM) has attracted more attention, lines of evidence showed that application of TCM improved AKI, while the mechanisms of action for some TCMs were well illustrated. However, reviews summarizing the progress in this field are still lacking. In this paper, we reviewed TCM preparations and TCM monomers in the treatment of AKI in recent 10 years, and described their renal protective effects and mechanisms of action which include alleviating inflammation, programmed cell death, necrosis and reactive oxygen species. By focusing on the mechanisms of TCMs to improve renal function, we provide the effective complementary and evidence for promoting the development of TCMs to treat AKI. Moreover, we also summarized the TCMs with nephrotoxicity, which provides a more comprehensive understanding of the TCMs in the treatment of AKI. This review may provide theoretical basis for the clinical application of TCMs in the future.